PENGARUH LOAN TO DEPOSIT RATIO, NET INTEREST MARGIN DAN INFLASI TERHADAP PROFITABILITAS - Sugiantari, Ni Luh Putu; Dana, I Made (E-Jurnal Manajemen; Vol 8 No 11 (2019)DO - 10.24843/EJMUNUD.2019.v08.i11.p07, 2019)
Profitability is the ability of a company to earn profits in relation to sales, total assets and own capital. ROA is chosen as the ratio of profitability, because ROA is used to measure the ability of bank management to obtain profits generated from the total assets of the bank concerned. The purpose of this study was to determine the effect of LDR, NIM, and Inflasi on Profitability (ROA). The study used a causal associative approach conducted at PT. Regional Development Bank of Bali for the period 2009-2017. The method of collecting data in research uses nonparticipant observation methods. The analysis technique used is multiple linear regression which is processed using the SPSS program. The results showed that the Loan to Deposit Ratio had a positive and not significant effect on ROA, Net Interest Margin had a positive and significant effect on ROA and Inflasi had a positive and not significant effect on ROA. Keywords : Inflation, LDR, NIM, profitability